Nisin penetration and efficacy against Staphylococcus aureus biofilms under continuous-flow conditions. Issue 7 (14th May 2019) - Godoy-Santos, Fernanda; Pitts, Betsey; Stewart, Philip S.; Mantovani, Hilario C.
Abstract : Biofilms may enhance the tolerance of bacterial pathogens to disinfectants, biocides and other stressors by restricting the penetration of antimicrobials into the matrix-enclosed cell aggregates, which contributes to the recalcitrance of biofilm-associated infections. In this work, we performed real-time monitoring of the penetration of nisin into the interior of Staphylococcus aureus biofilms under continuous flow and compared the efficacy of this lantibiotic against planktonic and sessile cells of S. aureus . Biofilms were grown in Center for Disease Control (CDC) reactors and the spatial and temporal effects of nisin action on S. aureus cells were monitored by real-time confocal microscopy. Under continuous flow, nisin caused loss of membrane integrity of sessile cells and reached the bottom of the biofilms within ~20 min of exposure. Viability analysis using propidium iodide staining indicated that nisin was bactericidal against S. aureus biofilm cells. Time-kill assays showed that S. aureus viability reduced 6.71 and 1.64 log c.f.u. ml -1 for homogenized planktonic cells in exponential and stationary phase, respectively. For the homogenized and intact S. aureus CDC biofilms, mean viability decreased 1.25 and 0.50 log c.f.u. ml -1, respectively. Our results demonstrate the kinetics of biofilm killing by nisin under continuous-flow conditions, and shows that alterations in the physiology of S. aureus cells contribute to variations in sensitivity to the lantibiotic. The approach developed here could be useful to evaluate the antibiofilm efficacy of other bacteriocins either independently or in combination with other antimicrobials.